The square as the epicenter of local development - Felipe Lucca (European Regional Science Association (ERSA), 2011)
There is no denying that the capital has penetrated too deep and far away in body and soul of the people, in their intelligence, psyche and imagination, in their core of 'vitality'; and while such 'vitality' has become the primary source of value in capitalism. In addition to this, the dramatic centralization of political and economic power that characterizes our way of organizing society leads, ultimately, a deep divorce between the citizen's requirements and the content of economic and social development. The local empowerment emerges as a new way to aggregate, create meaning, invent devices for appreciation and self-respect; and also an important tool that can facilitate the organized expression of community needs and assist in setting democratic priorities of local development. There is no doubt that something new is emerging in various parts of the territory in Sao Paulo - the biggest city of Brazil, with over eleven billion people. It is remarkable that there is a growing desire and political will of the inhabitants to relinquish their passive attitudes and assume, collectively, the changes in favor of the creation of improved living conditions of the neighborhood. In an area comprising four neighborhoods of the west Sao Paulo it was identified three social experiences that follows singular paths, but have the same goal: promoting the improvement of the square nearby their homes and, thereby, encourage the use of public space. The aim of this report is to analyze these three social experiences and compare them with the concept of local development. To support this essay, it was made a literature review on the concept of Development and Local Development based, fundamentally, on the ideas of Amartya Sen, Ladislau Dowbor, Ignacy Sachs, Celso Furtado and Alain Lipietz. The author of this essay participated actively in the three social experiments from February to December 2010 producing 'thick descriptions' (GEERTZ, 1989) about the meetings, the dynamics of neighborhoods and squares and informal conversations with participants. This essay concludes that the square in the urban territory can symbolize the epicenter of local development.
Keywords: 330; social experiences; square; local empowerment; local development